Nutrition counseling and education skills a practical guide - Beto, Judith A.; Holli, Betsy B. (Philadelphia Wolters Kluwer Health, 2024)
"Nutrition Counseling and Education Skills: A Guide for Professionals helps students develop the communications, counseling, interviewing, motivational, and professional skills they'll need as Registered Dietitian professionals. Throughout the book, the authors focus on effective nutrition interventions, evidence-based theories and models, clinical nutrition principles, and knowledge of behavioral science and educational approaches"
Expanding scope of nutrition practice -- Communication -- Interviewing -- Communication and cultural competence -- Stages and processes of health behavior change -- Person-centered counseling -- Counseling for behavior modification -- Counseling for cognitive change -- Principles and theories of learning -- Planning learning -- Implementing and evaluating learning -- Delivering oral presentations -- Using instructional media -- Facilitating group learning.
Preceded by Nutrition counseling and education skills / Betsy B. Holli, Judith A. Beto. Philadelphia : Wolters Kluwer Health, [2018].
Includes bibliographical references and index.
Keywords: Communication in diet therapy; Patient education; Interpersonal communication